HUBUNGAN DISIPLIN DAN MOTIVASI KERJA DENGAN KINERJA GURU DALAM MENGAJAR IPS DI MADRASAH IBTIDAIYAH KABUPATEN GARUT - Muhammad Nurjamaludin (Universitas Pendidikan Indonesia, 2020)
The purposes of this study was to know whether there is a positive influence between working motivation towards teachers’ performance of social study in the Madrasah Ibtidaiyah in Karangpawitan District, Garut. The method used in this research is descriptive quantitative method with a number of samples of 120 teachers. The instruments are compiled in these study as many as 60 items of three variables. From the results of research show that F count of 25.091, since F count (25.091) F table 3.07, then Ho is rejected. It can be concluded that there is simultaneously a significant influence on working discipline and working motivation on the teachers’ performance in teaching social study. The magnitude of the effect of variable discipline and motivation influence 30% of the teaching performance of teachers while the remaining 70% is contributed by other variables not examined in this study.